How to perform transcystic stenting in the COVID‐19 pandemic: an approach to biliary stenting without specialized endobiliary stenting equipment. Issue 6 (15th March 2021) - Joseph, Maria; Gaszynski, Rafael; Bender, Kyle; Daly, Daniel; Merrett, Neil; Apostolou, Christos
Abstract : Management options for common bile duct stones found at laparoscopic cholecystectomy (LC) includes concurrent transcystic biliary stenting, effectively providing a conduit for common bile duct drainage and improving the success of subsequent endoscopic retrograde cholangiopancreatography. In the unprecedented COVID‐19 pandemic however, potential disruptions to the medical supply chain have been far reaching, including the distribution of specialised biliary stent sets. To overcome this, we devised an innovative method at our centre to substitute traditional procedural stent sets by employing standard, universally accessible open‐ended ureteral catheters, jagwires and pancreatic or biliary stents with similar procedural success.